Challenges and opportunities of gender mainstreaming strategy implementation in public sectors: The case of Women and Children Affairs Office, Bahir Dar City Administration, Amhara Region, Ethiopia. Issue 2 (20th August 2021) - Mihrete, Alemeneh G.; Bayu, Eyayu K.
Abstract: Gender Mainstreaming is an organizational strategy to bring a gender perspective to all aspects of an institution's policy. This research aimed to investigate the challenges and opportunities of gender mainstreaming implementation by taking women, children, and youth affairs office of Bahir Dar City administration as a case. To do so, a qualitative research method with a case study research design was employed. To select the participants, purposive and availability sampling techniques were employed. Interview, focus group discussion, and document review were used as major data collection instruments. The data were analyzed thematically. The findings revealed that, absence of gender focal person, compartmentalization, lack of commitments, lack of training, lack of theoretical and technical skills about gender, and insufficient budget were the identified challenges. The presence of evaluation among heads at the council, existence of policies, and cooperative leadership were identified as an opportunity. To sum up, there are numerous challenges that hinder its monitoring and evaluation activities to mainstream gender even if there were a few opportunities that facilitate their activities. Based on the findings, the regional government should support and monitor the respective office challenges. Resumen: La transversalización de género es una estrategia organizacional para traer una incorporación con perspectiva de género a todos los aspectos de la política de una institución. Esta investigación tuvo como objetivo investigar los desafíos y oportunidades de la implementación de la transversalización de género tomando como caso la oficina de asuntos de mujeres, niños y jóvenes de la administración de la ciudad de Bahir Dar. Para ello, se empleó un método de investigación cualitativa con un diseño de investigación de estudio de caso. Para seleccionar a los participantes, se emplearon técnicas de muestreo intencional y de disponibilidad. La entrevista, la discusión de grupos focales y la revisión de documentos se utilizaron como principales instrumentos de recopilación de datos. Los datos se analizaron temáticamente. Los hallazgos revelaron que la ausencia de una persona focal de género, la compartimentación, la falta de compromisos, la falta de capacitación, la falta de habilidades teóricas y técnicas sobre género y el presupuesto insuficiente fueron los desafíos identificados. La presencia de evaluación entre los jefes del consejo, la existencia de políticas y el liderazgo cooperativo se identificaron como una oportunidad. En resumen, existen numerosos desafíos que dificultan sus actividades de monitoreo y evaluación para incorporar la perspectiva de género aun cuando haya pocas oportunidades que faciliten sus actividades. Con base en los hallazgos, el gobierno regional debe apoyar y monitorear los desafíos institucionales correspondientes. 摘要: 性别主流化是一项组织策略, 用于为机构政策的各个方面提供性别视角。本研究旨在以巴赫达尔城市管理局妇女、儿童和青年事务办公室为例, 调查性别主流化战略实施的挑战和机遇。为此, 应用了包含一项案例研究设计的定性研究法。应用立意抽样和可得性抽样法选择参与者。主要数据收集工具为访谈、焦点小组讨论和文献综述。对数据进行了主题分析。研究发现表明, 所识别的挑战包括:缺乏性别课题联络人、心理区隔化、缺乏承诺、缺乏培训、缺乏关于性别的理论技能和技术技能、预算不足。所识别的机遇包括:委员会领导之间的评价、相关政策的存在、合作式领导力。总而言之, 即使存在一些能促进性别主流化活动的机遇, 也存在许多挑战阻碍性别主流化的监督活动和评价活动。基于这些发现, 地区政府应提供支持并监督各自的性别事务办公室所存在的挑战。